Whole-genome sequencing and evolutionary analysis of the wild edible mushroom, Morchella eohespera - Li, Yixin; Yang, Ting; Qiao, Jinxia; Liang, Jian; Li, Zhonghu; Sa, Wei; Shang, Qianhan (Frontiers in Microbiology, 2024)
Morels (Morchella, Ascomycota) are an extremely desired group of edible mushroom with a worldwide distributions. Morchella eohespera is a typical black morel species, belonging to the Elata clade of Morchella species. The biological and genetic studies on this mushroom is rare, largely hindering the studies of molecular breeding and evolutionary aspects. Herein, we performed de novo sequencing and assembly of M. eohespera strain m200 genome using the third generation Nanopore sequencing platform. The whole genome size of M. eohespera was 53.81 Mb with a contig N50 of 1.93 Mb, and the GC content was 47.70%. A total of 9,189 protein-coding genes were annotated. Molecular dating showed that M. eohespera differentiated with its relativer M. conica at ~19.03 Mya (million years ago) in Burdigalian. Evolutionary analysis showed that 657 gene families were contracted and 244 gene families expanded in M. eohespera versus the related morel species. The non-coding RNA prediction results showed that there were 336 tRNAs, 76 rRNAs, and 45 snRNAs in M. eohespera genome. Interestingly, there was a high degree of repetition (20.93%) in M. eohespera genome, and the sizes of long interspersed nuclear elements, short interspersed nuclear elements and long terminal repeats were 0.83 Mb, 0.009 Mb and 4.56 Mb, respectively. Additionally, selection pressure analysis identified that a total of 492 genes in M. eohespera genome have undergone signatures of positive selection. The results of this study provide new insights into the genome evolution of M. eohespera, and lay the foundation for in-depth research of the molecular biology of the genus Morchella in the future.